Happiness and satisfaction research pre and during the COVID-19 pandemic: A bibliometric analysis of global scientific literature - Pang, Nicholas Tze Ping; Kamu, Assis; Guan, Teik Ee; Sombuling, Agnis; Ho, Chong Mun; Noor Hassline, Mohamad; Wider, Walton; Muhammad Ashraf, Fauzi (F1000 Research Ltd., 2023)
Background: The study provides a comprehensive analysis of trends of global scientific research, comparing pre-coronavirus disease (COVID 19) and during COVID-19 research in happiness and satisfaction, from 2014 up to 2021. Methods: The study period of the current research was divided into two phases, before the COVID-19 pandemic (1998 documents) and during COVID-19 (2020 until December 18, 2021). The Scopus database was comprehensively searched on relevant publications on Happiness and Satisfaction. Only articles published in English were retrieved. Bibliometric indicators were analyzed using Bibliometrix, an R package, and VOSviewer. Var1.6.6. Bibliometric indicators include the year of publications, authors, region, subject areas, countries, institutions, journals, country collaboration. Authorship productivity was presented in the final analysis. Results: A total of 3069 documents were extracted from Scopus. Overall, articles retrieved were written by 5220 authors before COVID-19 (2014-2019) and 3520 authors during COVID-19 (2020-2022), published in 2593 journals, with 83 counties represented before COVID-19 and 84 during COVID-19, and 21.66 average citations per document before COVID-19 and 30.4 average citations per document during COVID-19. Journal of Happiness Studies led in the number of articles produced. University of California was the most productive institution both before (number of publications [NP] = 42) and during (NP = 19) the COVID-19 pandemic. The US was the most productive country on multiple metrices; firstly, based on the most productive country both before (NP = 341) and during the pandemic (NP = 145), and secondly, based on the multiple country publications metric both before (NP = 34) and during the pandemic (NP = 34). Conclusions: This bibliometric study demonstrates that the COVID-19 pandemic has not significantly affected the productivity of happiness and satisfaction researchers; however, there are subtle changes in thematic evolution that will probably inform the direction of happiness research in the coming decade.